Total synthesis of cajanine and its antiproliferative activity against human hepatoma cells - Xing-yue Ji; Si-tu Xue; Guang-hui Zheng; Yan-xing Han; Zong-ying Liu; Jian-dong Jiang; Zhuo-rong Li (Elsevier, 2011)
Cajanine, a constituent of Cajanaus cajan L., used in traditional Chinese medicine, is a promising drug candidate because of its broad range of bioactivities. However, the total synthesis of cajanine and its derivatives has never been reported. Herein, we report the total synthesis of cajanine in nine steps with an overall yield of 10% together with its analog, longistyline A, in 8% yield. The antiproliferative activity of the two compounds against a human hepatoma cell line is also reported.